2022
DOI: 10.1136/jim-2021-002270
|View full text |Cite
|
Sign up to set email alerts
|

Specific Changes of Erythroid Regulators and Hepcidin in Patients Infected by SARS-COV-2

Abstract: Iron metabolism is tightly linked to infectious and inflammatory signals through hepcidin synthesis. To date, iron homeostasis during SARS-CoV-2 infection has not yet been described. The aim of this study is to characterize the hepcidin and erythroid regulators (growth differentiation factor 15 (GDF-15) and erythroferrone (ERFE)) by measuring concentrations in plasma in context of COVID-19 disease.We performed a single-center observational study of patients with COVID-19 to evaluate concentrations of main regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Recently, Peng et al have found higher hepcidin and ferritin levels and lower iron levels in severe COVID-19 patients [ 49 ]. Meanwhile, the report by Delaye et al shows that higher hepcidin levels are critical in patients with COVID-19 compared to in non-COVID-19 patients with similar CRP levels [ 50 ]. Growing evidence has revealed that multisystem inflammatory syndrome associated (MIS-C) with COVID-19 in children shares many clinical features [ 51 ] and inflammatory responses with KD [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Peng et al have found higher hepcidin and ferritin levels and lower iron levels in severe COVID-19 patients [ 49 ]. Meanwhile, the report by Delaye et al shows that higher hepcidin levels are critical in patients with COVID-19 compared to in non-COVID-19 patients with similar CRP levels [ 50 ]. Growing evidence has revealed that multisystem inflammatory syndrome associated (MIS-C) with COVID-19 in children shares many clinical features [ 51 ] and inflammatory responses with KD [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Though higher hepcidin level was found in cases than that in controls, the difference was not significant (SMD (95%CI): 0.750 (−0.805, 2.306); Z = 0.95 p for Z = 0.345; I 2 = 96.40%, p for I 2 < 0.001; Table 3, Figure 9). [10,18,20,24] on hepcidin levels in COVID-19 cases and controls. The solid diamond and horizontal line represent the study-specific effect and 95%CI, respectively; the size of the grey square is positively correlated with the weight distributed to each study in the meta-analysis.…”
Section: Tibc Tsat and The Mortality Of Covid-19mentioning
confidence: 99%
“…Previous studies have investigated the relationships among iron, ferritin, hemoglobin, hepcidin, TIBC, TSAT and COVID-19, but their results are conflicting and inconsistent. Most studies about serum iron have shown that lower iron levels are found in more at-risk groups, such as non-survivors compared to survivors [8][9][10][11][12][13], severe disease groups compared to non-severe disease groups [10,[13][14][15][16] and cases to controls [10,[16][17][18][19][20][21], whereas others expressed the opposite results [7,22,23]. In all relevant studies, the hemoglobin levels were found to be lower in severe groups than those in controls [7,10,24] or non-severe groups [22,[25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations